The Hague Conference on private international law “Judgments Convention”: study - Miguel Asensio, Pedro Alberto de; Cuniberti, Gilles; Franzina, Pietro; Heinze, Christian; Requejo Isidro, Marta (European Parliament, Directorate-General for Internal Policies, Policy Department for Citizens' Rights and Constitutional Affairs, 2018)
This study, commissioned by the European Parliament's Policy Department for Citizens' Rights and Constitutional Affairs at the request of the JURI Committee, provides an assessment of the ongoing work of the Hague Conference on the Judgments Convention. The analysis focuses on the November 2017 Draft Convention, its interplay with international and Union instruments in the field, as well as its potential future impact on the regulation of civil and commercial cross-border disputes.
Gesehen am 16.08.2018
Manuscript completed in April 2018
Keywords: Judgments Convention